IMAGINING ACCESS FOR ALL: THE FAILED INTRODUCTION OF A NEW EDITING INTERFACE FOR WIKIPEDIA - Osman, Kim (AoIR Selected Papers of Internet Research, 2015)
Wikipedia, the free online encyclopaedia, is built on shared ideals and values about access to knowledge. However active participation in the platform is declining and new editors are decreasingly likely to be retained as committed volunteers to the vision of making “the sum of all knowledge” freely available (Halfaker, Geiger, Morgan, & Riedl, 2012; Wikipedia, 2014). In response to this and issues around usability, the Wikimedia Foundation developed VisualEditor – a “what you see is what you get” (WYSIWYG) editor for Wikipedia – to replace the existing wiki markup editor. VisualEditor was rolled out as the default editing interface for all users on English Wikipedia on July 1, 2013. It was turned off as the default interface on September 23, 2013.